The Transformation of Umrah Savings Group Practices at PT Arofah Syam Al-Hadi: A Controversial Analysis in the Perspective of Sharia Economic Law - miftahussurur, wildan; Halili, Halili (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2025)
The practice of umrah arisan in PT Arofah Syam Al-Hadi has become a social phenomenon that attracts the attention of the community in Sukosari Village, Sukowono District, Jember Regency. With the increasing interest of the community to perform the Umrah pilgrimage, Arisan Umroh emerged as an alternative solution that offers convenience in collecting funds. This research aims to analyze the practice of arisan umroh from the perspective of sharia economic law with a case study at PT arofah Syam Al-Hadi. This research uses a qualitative method with a descriptive approach. The data obtained from the results of this study using observation, interviews and documentation with sharia economic law experts and umroh arisan managers. Data and data sources used in this research are primary data sources and secondary data sources. The practice of umroh arisan in PT Arofah Syam Al-Hadi Sukosari Village, Sukowono District, Jember Regency is carried out based on an agreement made at the beginning between arisan members and other members. After the agreement is reached by explaining the procedure, then the umroh arisan is carried out. Viewed from the perspective of Sharia Economic Law on the Umrah Arisan Practice of PT Arofah Syam Al-Hadi in Sukosari Village, Sukowono District, Jember Regency in accordance with Islamic law because the system applied has fulfilled the terms and conditions of the Wadi'ah contract. PT Arofah Sham Al-Hadi has explained the agreement before the Wadi'ah contract including the details of the Umrah arisan installments and the benefits of the savings.